The determination of the axial Young's modulus of honeycomb specimens under bending. Issue 1 (5th September 2017) - Drach, Andrew; Kovar, Desiderio; Mikulak, James K.; Rodin, Gregory J.
Abstract: For solid specimens, Young's modulus is commonly determined from straightforward uniaxial tension experiments. However, honeycomb specimens are far more challenging to test in tension, and it is therefore desirable to conduct bending experiments to determine Young's modulus. The premise of this work is that the bending response of honeycomb specimens may be significantly different from that of solid specimens, and therefore it is necessary to establish a sound protocol for the determination of the axial Young's modulus of honeycomb specimens under bending. Toward this goal, we present results of a study that combines experimental, finite element simulation, and classical beam theory approaches. These results confirm that accurate measurements of Young's modulus of honeycombs require careful consideration of the specimen geometry and analysis of the data. We demonstrate that the use of conventional Bernoulli‐Euler's beam theory to interpret the data requires very slender specimens. We also show that less slender specimens can be used if the experimental data is interpreted on the basis of three‐dimensional elasticity theory and numerical simulations. A third option is to use a combination of moderately slender specimens and Timoshenko's beam theory.